Comparison of Fresh Palm Fruit Bunch Production Estimates using The Black Bunch Fruit Census Method Between The Costarica and Sriwijaya Varieties - Maulana, Abbi; Afriani, Siti Rakhmi; Junainah; Yusticia, Stenia Ruski; M. Rezky Galang; Bagas Saputra (Jurnal Riset Perkebunan, 2025)
Palm oil is a strategic commodity that plays an important role in supporting Indonesia's economic growth. In several companies, different oil palm varieties are cultivated, including Costarika and Sriwijaya 1. Production fluctuations among these varieties underscore the importance of applying the black bunch census method in yield estimation. This study aims to estimate the future production of Fresh Fruit Bunches (FFB) between the Costarika and Sriwijaya 1 varieties. The research method employed was the black bunch census conducted on both varieties (Costarica and Sriwijaya 1). The observed parameters included the average bunches per palm and tonnage of the two varieties. Data analysis was performed using normality tests and independent t-tests. The results showed that the Sriwijaya 1 variety had the highest average bunches per palm at 4.36 and the highest production tonnage at 181,684 kg. However, further independent t-tests indicated that there was no significant difference between the Costarika and Sriwijaya 1 varieties in terms of average bunches per palm and total tonnage produced.